2017
DOI: 10.3390/g8020021
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Triggers of Conflict and Emotional Reactions

Abstract: Abstract:We study three triggers of conflict and explore their resultant emotional reactions in a laboratory experiment. Economists suggest that the primary trigger of conflict is monetary incentives. Social psychologists suggest that conflicts are often triggered by fear. Finally, evolutionary biologists suggest that a third trigger is uncertainty about an opponent's desire to cause harm. Consistent with the predictions from economics, social psychology, and evolutionary biology, we find that conflict origina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…14 A typical prediction for contests is that agents compete at the level where marginal benefit of winning the contest equals to the marginal cost of competing. An experimental literature, however, finds that for most (though not all) competition is more aggressive than predicted (see [28] for review) and that more frequent conflict increases negative emotions [143]. It is a long-standing puzzle why participants compete more than predicted [144].…”
Section: Staying Awake Vs Sleepingmentioning
confidence: 99%
“…14 A typical prediction for contests is that agents compete at the level where marginal benefit of winning the contest equals to the marginal cost of competing. An experimental literature, however, finds that for most (though not all) competition is more aggressive than predicted (see [28] for review) and that more frequent conflict increases negative emotions [143]. It is a long-standing puzzle why participants compete more than predicted [144].…”
Section: Staying Awake Vs Sleepingmentioning
confidence: 99%
“…They are considered the cause of an emotional reaction or outburst. Also, emotional triggers are often perceived as uncontrollable reactions and the cause of inner conflicts (Caldara, McBride, McCarter & Sheremeta, 2017). Managing, not suppressing or avoiding, emotions is the key to a functional and successful communication.…”
Section: Empathic Communicationmentioning
confidence: 99%
“…For instance, authors investigate the way emotions drive such behavior in relation to social ties [ 54 ], fairness perceptions and experienced emotions [ 55 ], waiting time [ 56 ], the demand for expressing emotions [ 57 ] and negative emotions [ 58 ]. In the same vein, using the JoD game, Caldara et al [ 59 ] found that negative emotions, generated by the game, increase the destroyed amount. Based on the literature above, the mentioned games are responsible of triggering a range set of emotions susceptible of influencing spiteful behavior.…”
Section: Introductionmentioning
confidence: 99%